2019
DOI: 10.1101/803924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GABA-ergic dynamics in human frontotemporal networks confirmed by pharmaco-magnetoencephalography

Abstract: To bridge the gap between preclinical cellular models of disease and in vivo imaging of human cognitive network dynamics, there is a pressing need for informative biophysical models. Here we assess dynamic causal models (DCM) of cortical network responses, inverted to magnetoencephalographic observations during an auditory oddball roving paradigm in healthy adults. This paradigm induces robust perturbations that permeate frontotemporal networks, including an evoked ‘mismatch negativity’ response and transientl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…By regulating the strength of inhibition, the self-connections allowed for sustained activity in the cortex while maintaining a balance between excitation and inhibition throughout the network. A recent magnetoencephalography study using DCM showed that a GABA A reuptake inhibitor altered the strength of inhibitory (self-)connections in humans 26 , indicating that the DCM framework could be used to study the effect of therapeutic interventions on (self-)inhibition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By regulating the strength of inhibition, the self-connections allowed for sustained activity in the cortex while maintaining a balance between excitation and inhibition throughout the network. A recent magnetoencephalography study using DCM showed that a GABA A reuptake inhibitor altered the strength of inhibitory (self-)connections in humans 26 , indicating that the DCM framework could be used to study the effect of therapeutic interventions on (self-)inhibition.…”
Section: Methodsmentioning
confidence: 99%
“…The strength of intrinsic self-inhibition can thus be interpreted as a proxy for the regional excitation/inhibition balance 25 . Recently, a study using magnetoencephalography showed that DCM can quantify the increase in tonic inhibition by a GABA reuptake inhibitor 26 . Here, we use spDCM to study the effects of pharmacotherapy and ECT on extrinsic and intrinsic effective connectivity in severely depressed patients.…”
Section: Mainmentioning
confidence: 99%
“…Tiagabine binds selectively and with high affinity to the GABA reuptake transporter GAT1 elevating the level of GABA in the extracellular fluid and synapse. 34 In health, tiagabine alters beta power widely across the cortex, 35,36 and enhances movement related beta ERD/ERS 37 . However, the behavioural consequences of pharmacologically altering beta are unclear; Muthukumaraswamy et al, 37 reported no drug induced changes in movement performance in their group of young healthy adults although there were observed changes in beta power.…”
Section: Introductionmentioning
confidence: 99%